IL-10 Deficiency Accelerates Type 1 Diabetes Development via Modulation of Innate and Adaptive Immune Cells and Gut Microbiota in BDC2.5 NOD Mice - Huang, Juan; Tan, Qiyuan; Tai, Ningwen; Pearson, James Alexander; Li, Yangyang; Chao, Chen; Zhang, Lucy; Peng, Jian; Xing, Yanpeng; Zhang, Luyao; Hu, Youjia; Zhou, Zhiguang; et al. (Frontiers in Immunology, 2021)
Type 1 diabetes is an autoimmune disease caused by T cell-mediated destruction of insulin-producing β cells. BDC2.5 T cells in BDC2.5 CD4+T cell receptor transgenic Non-Obese Diabetic (NOD) mice (BDC2.5+ NOD mice) can abruptly invade the pancreatic islets resulting in severe insulitis that progresses rapidly but rarely leads to spontaneous diabetes. This prevention of diabetes is mediated by T regulatory (Treg) cells in these mice. In this study, we investigated the role of interleukin 10 (Il-10) in the inhibition of diabetes in BDC2.5+ NOD mice. We generated Il-10-deficient BDC2.5+ NOD mice (BDC2.5+Il-10-/- NOD mice) to investigate the potential role of IL-10. Our results showed that BDC2.5+Il-10-/- NOD mice displayed robust and accelerated diabetes development. We found that Il-10 deficiency promoted the generation of neutrophils in the bone marrow and increased the proportions of neutrophils in the periphery (blood, spleen, and islets), and was mediated by altered intestinal immunity and the gut microbiota composition in BDC2.5+ NOD mice. In vitro studies showed that the gut microbiota from BDC2.5+Il-10-/- NOD mice can expand neutrophil populations. Moreover, in vivo studies demonstrated that the depletion of endogenous gut microbiota by antibiotic treatment decreased the proportion of neutrophils. Although Il-10 deficiency in BDC2.5+ NOD mice had no obvious effects on the proportion and function of Treg cells, it affected the immune response and activation of CD4+ T cells. Moreover, the pathogenicity of CD4+ T cells was much increased, and this significantly accelerated the development of diabetes when these CD4+ T cells were transferred into immune-deficient NOD mice. Our study provides novel insights into the role of IL-10 in the modulation of neutrophils and CD4+ T cells in BDC2.5+ NOD mice, and suggests important crosstalk between gut microbiota and neutrophils in type 1 diabetes development.